Primary vaccination with low dose live dengue 1 virus generates a proinflammatory, multifunctional T cell response in humans. - Janet C Lindow; Nathan Borochoff-Porte; Anna P Durbin; Stephen S Whitehead; Kelly A Fimlaid; Janice Y Bunn; Beth D Kirkpatrick (Public Library of Science (PLoS), 2012)
The four dengue virus serotypes (DENV-1-DENV-4) have a large impact on global health, causing 50-100 million cases of dengue fever annually. Herein, we describe the first kinetic T cell response to a low-dose DENV-1 vaccination study (10 PFU) in humans. Using flow cytometry, we found that proinflammatory cytokines, IFNγ, TNFα, and IL-2, were generated by DENV-1-specific CD4(+) cells 21 days post-DENV-1 exposure, and their production continued through the latest time-point, day 42 (p<0.0001 for all cytokines). No statistically significant changes were observed at any time-points for IL-10 (p = 0.19), a regulatory cytokine, indicating that the response to DENV-1 was primarily proinflammatory in nature. We also observed little T cell cross-reactivity to the other 3 DENV serotypes. The percentage of multifunctional T cells (T cells making ≥ 2 cytokines simultaneously) increased with time post-DENV-1 exposure (p<0.0001). The presence of multifunctional T cells together with neutralizing antibody data suggest that the immune response generated to the vaccine may be protective. This work provides an initial framework for defining primary T cell responses to each DENV serotype and will enhance the evaluation of a tetravalent DENV vaccine.